EFL Students’ Voices on Collaborative Strategic Reading: A Qualitative Study of Perception and Motivation in Reading Class - Safitri, Citra Dwi; A. Kamariah; Musdalifah; Jaya, Muhammad Fahri (ARRUS Journal of Social Sciences and Humanities, 2025)
Reading plays a critical role in English as a Foreign Language (EFL) context, serving not only as a core linguistic skill but also as a gateway to academic success. This study explores EFL students’ perceptions of Collaborative Strategic Reading (CSR) and examines its influence on their motivation to engage in reading activities. Using a qualitative descriptive design, the data were collected from fifth-semester students enrolled in the Critical Reading course at Universitas Negeri Makassar through questionnaires and interviews. The findings revealed that students generally perceived CSR positively, recognizing its benefits in improving comprehension, clarifying complex texts, and promoting active participation. The CSR stages of preview, click & clunk, get the gist, and wrap up were largely seen as clear and practical, though some initial confusion was noted. Moreover, CSR fostered students’ engagement and enjoyment by creating an interactive and collaborative learning environment. Importantly, the strategy significantly boosted students’ reading motivation, both intrinsically and extrinsically, by making reading more structured, enjoyable, and socially rewarding. Further research could explore its long-term effects on academic achievement and its adaptability across different language proficiency levels.